Adaptable Architecture for the Digital Transformation of the Cameroonian University Ecosystem: A FORM/BCS Approach - Ngoumou, Amougou (CV. Media Digital Publikasi Indonesia, 2024)
The university education ecosystem in most developing countries where demographics are evolving exponentially, faces the problem of the massification of education with its corollaries in terms of teacher shortages and deterioration in the quality of training, Cameroon is not left out. Faced with this situation, most stakeholders agree that the digital transformation of the ecosystem makes it possible to tackle this problem. Several solutions are proposed, ranging from the digitization of training materials downloadable by learners to the implementation of hybrid training combining the face-to-face model with distance training in direct streaming, including models “semi-face-to-face single-teacher multi-room synchronous” training courses, thus qualified because it would consist of exploiting ICT to allow the same teacher to be, through dedicated screens, simultaneously followed in several classrooms by learners with the possibility for the latter to communicate in real time with him thanks to judiciously positioned cameras. However, whatever the formula adopted, problems persist such as time which is not always sufficient, the shortage of teachers and insufficient infrastructure. Thus, this article, through the analysis of the proposed solutions and the use of the software product line engineering paradigm, proposes a formula and adaptable reference architecture for a computer system making it possible to deal with the problem of massification of teaching